Pressure distribution in hydrodynamic journal bearing with lubricants additives - Omer, M.A. (EDP Sciences, 2014)
In this paper, the effects of additives on the base lubricants has been investigated and reported, aiming for enhancement and the improvement of hydrodynamic journal bearing performance. A pair of additives volume fractions with a viscosity ratio were considered as blended with the base binder. A dimensionless pressure distribution with improved viscosity over the lubricant film has been identified. The results show an increase on the pressure distribution in response to increase in volume fraction of the additives. Â© 2014 Owned by the authors, published by EDP Sciences.